DOS GESTOS FUNDAMENTAIS ÀS ESPECIFICIDADES DA REGULAÇÃO DAS APRENDIZAGENS: MEDIAÇÕES DA FORMAÇÃO INICIAL DE PROFESSORES DE LÍNGUA INGLESA - ALMEIDA, EDAN LUIS DE (2020)
The interest in studying social and natural context involved in teaching has been increasing and thus contributing to understand and strengthen the area of teaching and learning. This study aims at investigating the fundamental didactic gestures mobilized in the mediation of the teaching processes developed by pre-service English language teaching (PSELTs), taking as object to be taught a didactic sequence of the genre infographic. For this purpose, we set three specific objectives: the first is to build the macrostructure and synopses from the work with teaching sequences of the APLIs; the second is to do a survey on the fundamental gestures mobilized in the practice of these PSELTs during the period of teaching; finally, we aim to categorize the gesture of local regulation according to PSELT mobilization. The guiding concepts that underlie our study are based on the theoretical-methodological assumptions of socio-discursive interactionism (ISD) (BRONCKART, 1999; 2006; 2008; SCHNEUWLY; DOLZ, 2004; 2009), in its expansion with regard to knowledge and teaching capacities ( HOFSTETTER; SCHNEUWLY, 2009; CRISTOVÃO; STUTZ, 2011; STUTZ, 2012), the clinic of activity (CLOT, 2006; TOGNATO, 2009) and didactic gestures (SCHNEUWLY, 2009; JORRO, 2002; SILVA, 2013; BUCHETON, 2014 ). The research involved a double context formed by the university and two public schools, with two high school classes and the data for the research were generated through the recording and transcription of twenty classes of two PSELTs, from the fourth year of an undergraduate course in English language, during the period of teaching, in the compulsory supervised internship discipline. The didactic sequences of the genre infographic used for analysis were developed by the PSELTs and are composed of initial evaluation, three modules, and final evaluation. Regarding the results, by means of the construction of the macrostructure and the synopses, we could notice that the fundamental didactic gestures work together and intrinsically and, furthermore, they are linked to language capacities and to teacher knowledge. The results also pointed to the possible categorization of the gesture of local regulation into five categories: use of L1 for the teaching of English language, use of the board for language visualization in written form, repetition, reiteration and question types. The outcomes contribute to realize that the study of the fundamental didactic gestures in the effective practice of the classroom can provide us a very detailed insight into various nuances of the English language teacher's métier, essentially about the mediations that aim to present the teaching objects to the students.